Analisa Kebutuhan English for Specific Purpose untuk Pendidikan Vokasi - Tanzir Masykar (VOCATECH: Vocational Education and Technology Journal, 2019)
Abstrak— Mata kuliah Bahasa Inggris pada pendidikan vokasi merupakan mata kuliah umum (MKU) wajib. Berbeda dengan pendidikan di universitas, pendidikan vokasi menuntut konten pengajaran suatu mata kuliah dalam bentuk konten praktis. ESP, English for Sepcific Purpose adalah salah satu cabang ilmu pendidikan Bahasa Inggris yang dapat diterapkan dalam mengembangkan MKU Bahasa Inggris pada pendidikan vokasi. Studi pustaka ini menganalisis beberapa jurnal dan buku yang berkaitan dengan ESP dan mewawancarai dosen Bahasa Inggris pada tingkat universitas untuk menentukan materi Bahasa Inggris yang sesuai untuk pendidikan vokasi. Hasil kerangka need analysis (NA) Basturkmen dan Dudley-Evans, St John, & Saint John, dipaparkan dan diuji dengan kebutuhan pendidikan vokasi jurusan mesin [1, 2]. Hasil kajian pustaka dan Analisa kebutuhan menunjukkan perlu adanya kurikulum, silabus, dan aktivitas berbeda untuk setiap jurusan pada pendidikan vokasi. Silabus Bahasa Inggris umum di perguruan tinggi tidak dapat dipakai sepenuhnya untuk kebutuhan pendidikan vokasi. Kata kunci: Analisa Kebutuhan, English for Specific Purposes, Bahasa Inggris Umum, Pendidikan vokasi Abstract— English courses in vocational education are compulsory general courses (MKU). In contrast to university education, vocational education demands the teaching content of a course in the form of practical content. ESP, English for Specific Purpose is one branch of English education that can be applied in developing the English course in vocational education. This literature study analyzes a number of journals and books related to ESP and English language lecturer studies at the university level to determine appropriate English material for vocational education. The results of the Basturkmen and Dudley-Evans, St John, & Saint John's framework of need analysis are presented and tested with the vocational education needs of across three majors [1, 2]. The results of the literature review and need analysis indicate the need for different curriculum, syllabus, and activities for each department in vocational education. The general English syllabus in universities cannot be fully applied for vocational education needs. Keywords: Needs analysis, English for Specific Purposes, General English, Vocational Education